Effect of Lengthening FSH Treatment on Super Stimulatory Response and Embryo Production in Sahiwal Cattle - Lalchhanhima, Khiangte; Honparkhe, Mrigank; Singh, Narinder; Malik, Vijay Singh; Kumar, Ajeet; Singh, Prahlad (The Indian Journal of Animal Reproduction, 2025)
The study evaluated the effect of lengthening of superstimulation protocol (4 Day vs 6 Day) on superovulatory response and embryo production in Sahiwal cows, there is no literature regarding this comparative evaluation. Sahiwal cows were randomly divided into two groups viz. short FSH group (Group1; 4D FSH; n=6) and long FSH group (Group 2; 6D FSH; n=6). Animals in both the groups were administered injection estradiol benzoate (@ 2 mg) and progesterone (@ 50 mg/ animal) intramuscularly along with insertion of an intravaginal device (progesterone device) on a random day of estrous cycle (Day 0). The FSH treatments were started 4 days later (i.e on the expected day of wave emergence). A dose of 200 mg FSH and 300 mg FSH divided equally over 8 (Group 1) and 12 doses (Group 2) IM were injected at 12-h intervals in group 1 and group 2 respectively. Prostaglandin F2α (500 ug cloprostenol inj.) was injected on Day 7 morning (Group 1) and Day 9 morning (Group 2) and CIDR was removed. In both the groups, hCG (3000 I.U) was administered after 12 h of CIDR removal and AI was done at 22-24 h of hCG treatment. The embryo recovery was done non-surgically on the 7th day from first A.I (i,e Day 16 for group 1 and Day 18 for group 2). The mean number (± SEM) of >8mm follicles on the day of estrus did not differ between groups (P= 0.06) and comparatively higher number of ovulations were detected in 6-day FSH group than 4-day FSH group (71.3±11.77 vs 80.5±7.69. P= 0.27 respectively) but not statistically signif icant. Total number of CL’s, embryos collected and transferable embryos were higher in number in the 6-day group as compared to 4 Day groups. In conclusion, extending FSH treatment resulted in a greater number of follicles acquiring the ability to ovulate with higher numbers of ovulations.